2015
DOI: 10.1210/jc.2015-2692
|View full text |Cite|
|
Sign up to set email alerts
|

Gestational Diabetes Impairs Human Fetal Postprandial Brain Activity

Abstract: Fetal postprandial brain responses were slower in the offspring of women with GDM. This might indicate that gestational diabetes directly affects fetal brain development and may lead to central nervous insulin resistance in the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 31 publications
4
53
2
1
Order By: Relevance
“…A total of 72 pregnant women were enrolled in this study. They took part in a trial examining fetal response latencies to auditory stimuli measured with fMEG before and during an OGTT . During the fMEG measurement, fetal and maternal MCG were recorded simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 72 pregnant women were enrolled in this study. They took part in a trial examining fetal response latencies to auditory stimuli measured with fMEG before and during an OGTT . During the fMEG measurement, fetal and maternal MCG were recorded simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…During the fMEG measurement, fetal and maternal MCG were recorded simultaneously. The results of fetal brain activity of 40 women taking part in the present study measured with fMEG were reported in a previously published paper …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even modest differences in food intake or food choices in early life can have lifelong repercussions, and the metabolic status of the mother during gestation influences the brain dynamics of the fetus (18). Obesity is most prevalent in lower socio-economic groups, and this is likely to reflect genetics (assortative mating), epigenetics and environmental factors.…”
Section: Early Life Experiencesmentioning
confidence: 99%
“…One interesting study recorded fetal brain activity triggered by glucose ingestion in healthy or GD pregnant subjects, and associated diabetes to a slower brain response of the offspring (Linder et al 2015). Using a STZ rat model, Jing et al (2014) found a decreased expression of IGF-1 and increased expression of insulin receptors in brains of E14, E16 and E18 fetuses from diabetic mothers, effects that were accompanied by reduced number of dendritic spines and smaller levels of the pre-synaptic protein synaptophysin.…”
Section: Memory and Brain Insulin Signalingmentioning
confidence: 99%